Morfologi dan Anatomi Bibit Alpukat Sambungan pada Stadia tumbuh Entres dan Metode Sambung Pucuk - Da Costa, Antonia Jessica Sherlyn; Hidayat, Ramdan; Santoso, Juli (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2022)
Avocado is a fruit crop that is commercial and potential to be widely cultivated. Market demand for avocado was increased so production of avocado seed must increase too by grafting. The problem of grafting is often found in the connection between scion and rootstock that showed like elephant foot phenomenon, so it was necessary to study the linkage process between scion and rootstock. This research leads up to an increased percentage of finished graft seedlings that were ready for planting in the field. This method used a factorial experiment consisting of 2 factors. The first factor was the stages of entres (flushing, endodormancy, and ecodormancy), and the second factor was the grafting method (cleft graft, wedge graft, and splice graft). The research design used Complete Randomized Design with 4 replications and ANOVA with BNJ 5% test. The results showed all observations parameters interacted. Stage ecodormancy in splice graft resulted of vascular tissue (xylem and phloem) between scion and rootstock recovered better than other combination treatments by producing the best-grafted avocado seedlings growth with an increased percentage of grafted seedling by 42.50%, an interval of flushing by 4.91 days, and increased frequency of flushing by 1.83 times compared to stage flushing in cleft graft.